Massive Development of Nusantara Capital City in the Perspective of Ecological Politics - Bangun, Immanuel Christwo (Langgas: Jurnal Studi Pembangunan, 2024)
The development of the Capital City of Nusantara (IKN) in East Kalimantan is one of the most ambitious projects in Indonesia's modern history. Through a Political Ecology approach, this paper highlights how power and political dynamics shape interactions between humans and the environment and influence policies and practices that impact the exploitation of natural resources. The research method used is descriptive qualitative, with data collection through literature study. The development of IKN is not only influenced by political decisions that often ignore environmental aspects but also by the constellation of government that tends to be authoritarian and unconstitutional. This is reflected in the process of drafting the IKN law, which invited various polemics and questioned its legality. In the end, IKN development has the potential to damage the environment and deepen social injustice due to political practices that are not inclusive and democratic.